Phenotypic Identification and Molecular Characterization of Aspergillus Niger, Fumonisin and Ochratoxin Genes from Otomycosis in Domestic Cats with Special Emphasis to Underlying Risk Factors - Rusul Muayad Had; Ali Ibrahim Ali Al-Ezzy; Ahmed Hanash Khlaf AL-Zuhairi (Diyala Journal for Veterinary Sciences, 2025)
The current study aims to isolation of Aspergillus niger from external ear of cats, molecular characterization of A. niger, fumonisin and ochratoxin by conventional PCR and detection of risk factors. A total of 106 external ear swabs were taken from domestic cats and cultured on Sabouraud dextrose agar. Positive fungal growth was identified by conventional PCR using species-specific PCR primer pairs for A. niger (NIG1) and (Cmd A)—production of fumonisin and ochratoxin confirmed by PCR using Fum 1 and PKS specific primers. The total of (20.75 %) swabs were A.niger positive by culture and PCR using ( NIG1) and (Cmd A) primers. Cats with age (2-6) months were frequently infected followed by those with (12- 16) months. Males represent (62.26%) while female represent (37.73%). A total of (15.09%) males were infected with A.niger versus (5.66%) for females . Females appear to be at risk of getting A. niger infection at (1.813) time than males. No significant correlation was reported between age, sex, body weight; breed; hair length; ear cleaning interval; bathing frequency; season and infection with A. niger. Fumonisin was detected in (41.17%) of A. niger isolates while ochratoxin was not detected.